Initial Reports of the Deep Sea Drilling Project 1980
DOI: 10.2973/dsdp.proc.58.126.1980
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Profiles in Deep-Sea Sediments: New Evidence for Bacterial Diagenesis at Great Depths of Burial

Abstract: The sediments penetrated on Leg 58 of the Deep Sea Drilling Project in the Philippine Sea represent long periods of geologic time during which depositional conditions apparently remained very constant.Organic carbon and nitrogen contents of the sediments decrease with increasing depth of burial, before leveling off at minimum values of about 0.05 to 0.10 per cent and 0.01 per cent, respectively. The depth at which the minimum values are reached varies from site to site, but ages of sediments corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1980
1980
1995
1995

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…The rate constant obtained (4.0/m.y.) is 3 to 5 times higher than that reported by Waples and Sloan (1980) for comparable organic-carbon-lean hemipelagic sediments in the Pacific (Leg 58). The reasons for the differences in the diagenesis rate constants between that Atlantic and Pacific sediments are not obvious.…”
Section: Kinetics Of Organic Carbon Diagenesiscontrasting
confidence: 51%
See 1 more Smart Citation
“…The rate constant obtained (4.0/m.y.) is 3 to 5 times higher than that reported by Waples and Sloan (1980) for comparable organic-carbon-lean hemipelagic sediments in the Pacific (Leg 58). The reasons for the differences in the diagenesis rate constants between that Atlantic and Pacific sediments are not obvious.…”
Section: Kinetics Of Organic Carbon Diagenesiscontrasting
confidence: 51%
“…The diagenetic transformation of organic matter is not limited to the zone of macrofaunal activity, however. Waples and Sloan (1980) showed that in a Pacific Ocean setting in which the depositional environment had remained constant for 15 m.y., carbon and nitrogen decreased exponentially with depth of burial as a result of diagenesis within the sediments. Claypool (in press) attributed an exponential decrease in TOC in Leg 78A sediments to diagenesis.…”
Section: Microbial Diagenesismentioning
confidence: 99%
“…It has been tempting to utilize C/N data generated on the Glomar Challenger as though the nitrogen measured were entirely organic (e.g., Waples and Sloan, 1980). As Arrhenius (1950), Stevenson and Cheng (1972), and Tucholke, Vogt, et al (1979) have noted, however, C/N ratios in sediments with low contents of organic matter may be strongly influenced by the inorganic nitrogen present as ammonia or as ammonium ion fixed on clays.…”
Section: Introductionmentioning
confidence: 99%
“…More probably, reaction within the sediment leads to a decrease in organic carbon content with advancing time or increasing depth of burial. The regular decrease of organic carbon content with depth in marine sediments has been studied in both shallow (0-5 m) cores (Heath et al, 1977;Mueller and Mangini, 1980) and in DSDP (0-500 m) cores (Waples and Sloan, 1980). In a variety of environments, each with relatively uniform sediment accumulation rates, the decrease in organic carbon with time is consistent with first-order decay at half-lives that range from 15,000 to 866,000 years.…”
Section: Discussionmentioning
confidence: 90%